Biomechanical Determinants of Shooting Performance: The Role of Wrist and Elbow Joint Range of Motion in Male Basketball Players - Gözaçık, Yusuf (The European Research Journal, 2026)
Objectives: The aim of this study is to examine the relationship between wrist and elbow joint range of motion and shooting performance in young male basketball players. Methods: The research was conducted as a cross-sectional correlational study. The study sample consisted of 23 male basketball players residing in Diyarbakır, selected through purposive sampling. The wrist and elbow joint range of motion values, along with shooting performance scores of the athletes, were measured. Frequency analyses were performed, and after confirming the normality of the data distribution, Pearson correlation and multiple regression analyses were conducted. Results: According to the results, strong and significant positive correlations were observed between elbow flexion and pronation and shooting performance. In addition, elbow supination, as well as wrist flexion and extension, also showed statistically significant positive relationships with shooting performance. However, no significant relationship was found between shooting performance and radial deviation, ulnar deviation, or elbow extension. Conclusions: In conclusion, elbow joint range of motion appears to have a significant and determining effect on shooting performance in young male basketball players. In contrast, wrist mobility contributes to shooting performance to a more limited extent and therefore cannot be considered a direct determining parameter.